Clinical and laboratory criteria for diagnosis of bacterial vaginosis. Literature review - Gruzevskiy, A. A. (Journal of Education, Health and Sport, 2018)
The presence of bacterial vaginosis in women, especially for a long time, increases the risk of developing inflammatory diseases of the pelvic organs, creating serious problems after gynecological surgical interventions. In addition, bacterial vaginosis can be a cause of complications of pregnancy and childbirth, contributing to the miscarriage of pregnancy and premature birth. Bacterial vaginosis can lead to the development of chorioamnionitis, postpartum endometritis, intrauterine fetal infections, peritonitis. In addition, bacterial vaginosis is associated with infection of the urethral tract, cervicitis; is a risk factor for infection with sexually transmitted infections and HIV infection. In conditions of high pH there are favorable conditions for colonization of the genitourinary system by pathogenic microorganisms, as well as exacerbation of the latent course of viral infection of the urogenital tract. Mixed infections or infections developed on the background of severe imbalance in the vaginal microcenosis are observed in 20-30% of cases of clinically pronounced vaginal infections. Bacterial vaginosis negatively affects the quality of life of women. It is shown that in the presence of long-term and abundant discharge from the vagina in patients possible development of psychosomatic disorders, the trinity reduces performance, violates the sexual and childbearing functions, decreases the quality of life. The feature of bacterial vaginosis is its predisposition to relapse after treatment, which is observed in 50% of cases. Bacterial vaginosis is one of the most important factors in the development of inflammatory diseases of the pelvic organs and complications of pregnancy, in particular - the infection of amniotic fluid, as well as the formation of postoperative complications. Despite the various medical and prophylactic measures conducted in different countries, the reduction of the incidence of bacterial vaginosis is not noted, which makes the problem of finding new ways of effective diagnosis and treatment of bacterial vaginosis.